SIFAT KIMIA TANAH PADA BERBAGAI PENGGUNAAN LAHAN DI UB FOREST - Oktari Hermita Putri; Sri Rahayu Utami; Syahrul Kurniawan (Jurnal Tanah dan Sumberdaya Lahan, 2019)
Forest plays important roles including, ecology, social and economic, for the sustainability of life. UB Forest, as an example, is located at the foot slope of Mt. Arjuna. This study aimed at elucidating exploring soil chemical properties of the UB forest. Five different land uses i.e., protected areas (KL), pine + coffee (PK), pine + annual crop (PS), mahogany + coffee (MK), and mahogany + annual crop (MS) were selected for this study. Each land use was repeated three times. Inside of each plot (20 x 20 m2 size), three sub-plots (5 x 5 m2 size) were prepared randomly for soil and litter sampling. Soil samples were taken from every sub plot, at four different depths (0-10, 10-30, 30-50, 50-100 cm), and then composited for the respective depth. Soil chemical properties (CEC, pH, total N, available P, C, available bases, soil texture, and litter (thickness, dry weight) were measured. The results showed that land uses in UB Forest significant affected total N, and pH, but theyÂ  did not affect available P and CEC. The highest CEC was in KL. However, MS and MK tended to have high total, especially in the depth of 50-100cm.